Incidence of Muscular Strength, Anthropometry, and Asymmetry in the General Index of Autonomy in Older Chilean Women; [Incidencia de la Fuerza Muscular, Antropometría y Asimetría en el Índice General de Autonomía en Mujeres Mayores Chilenas] - Jofre-Saldia, E (Universidad de la Frontera, 2024)
Frailty affects the functional autonomy (FA) of older adults and could manifest itself in muscle imbalances in the limbs, resulting in a disparity in size and strength between them. In Chile, information on the relationship between muscle strength (MS) levels and FA asymmetries in older women is limited. This study related the levels of MS, anthropometric parameters, and asymmetries of the lower and upper limbs, with the FA of a group of older Chilean women. The study included 39 women who participated, and their FA was evaluated using the GDLAM index (IG). Based on the score obtained in the IG, they were classified by percentiles as Group 1 with favorable FA (P ≤ 50) and Group 2 with low FA (P > 50). Anthropometric parameters were BMI, fat percentage, bone mass, circumferences (arm, thigh, calf), diameters (humerus, femur) and upper/lower limb strength was evaluated to determine asymmetries. The differences between the covariates of both groups were evaluated using the student’s t test and the Mann-Whitney test for independent samples. G1 presented less asymmetry (p > 0.05) in the lower limbs and greater calf circumference than G2 (p < 0.05). G1 presented greater bilateral strength (dominant and non-dominant limb) compared to G2 (p < 0.05). The covariates of age, anthropometry, MS, and lower/upper limb asymmetries influence FA in older women. © 2024, Universidad de la Frontera. All rights reserved.